Investigation On Phase Shifting Effect On The Voltage Output Of Piezoelectric Cantilever Array - Bong, Yu Jing; Kok, Swee Leong (Institute Of Physics (IOP) Publishing, 2017)
This paper analyses the phase shifting of the output waveform produced by piezoelectric cantilevers under a range of vibration frequencies. The phase shift of four piezoelectric cantilevers with different resonant frequency are inspected while it is excited with the vibration from the electrodynamics shaker at a range of frequencies from 100 Hz to 500 Hz with the acceleration level (g-force) fixed at constant magnitude of 1g-level (9.81 m/s2). Time different and Lissajous pattern methods were used in this research to measure the phase shift of the output waveform. Both methods show similar result where the major phase shift happened at the resonant frequency of respective cantilevers. The phase difference remains low around 0 degrees or in other term in phase before the resonant frequency of the cantilever. When the frequency of the vibration source approaches the resonant frequency of respective cantilever, the phase different start to increase rapidly and reach 180 degree which is out of phase after the resonant frequency. This major phase shifting contributes to the significant rise of the gap in between the peaks formed when multiple piezoelectric cantilevers are connected together. As a result, it indirectly improves the output performance of the piezoelectric cantilevers array.